Implementation Analysis of Enterprise Risk Management (ERM) and Risk Mitigation Strategies in Securities Companies in the Digital Era - Zahra Devina Dewi; Ratu Aribah Santika Xaviera; Rara Marcella; Ahmad Devani Yuslah; Alfina Marta; Ahmad Setiawan Nuraya (Pasca Sarjana UKI, 2025)
This study aims to analyze the effectiveness of implementing Enterprise Risk Management (ERM) and operational risk mitigation strategies in securities companies in the digital era. Amid the high dependence on technology, disruptions to trading systems have become a serious threat to business stability. The research method uses a descriptive qualitative approach with primary data obtained through interviews and observations, as well as secondary data in the form of financial reports and capital market statistics. Risk analysis is carried out using a likelihood–impact matrix based on Financial Services Authority regulations. The results show that operational risks in the form of technical disruptions (glitches) in online trading applications and reputation risk occupy the highest risk level (high risk). System reliability, including the Sharia Online Trading System (SOTS), is proven to be a fundamental factor in maintaining investor confidence. In addition, disciplined risk management implementation contributes positively to net profit growth and long-term business sustainability. The study concludes that mitigation priorities must be focused on strengthening information technology infrastructure and enforcing credit risk control procedures in order to minimize financial losses.